Hubungan Dukungan Sosial Teman Sebaya dengan Resiliensi Siswa Korban Bullying - Khairunnisa, Nadia; Taufik, Taufik (Universitas Negeri Padang, 2023)
This research is motivated by the phenomenon of frequent acts of bullying in educational environments. Bullying is the aggressive and negative behavior of a person or group of people repeatedly with the aim of hurting the victim both physically and psychologically. As a result, many victims of bullying experience psychological disorders, for that they need to rise up with the support of their peers. This study aims to (1) describe the social support of peers for students who are victims of bullying, (2) describe the resilience of students who are victims of bullying, (3) examine the relationship between social support of peers and the resilience of students who are victims of bullying. This study uses a quantitative method with a descriptive correlational approach. The subjects of this study amounted to 24 students. The samples were drawn using saturated sample techniques. Data were analyzed using the Spearman rho correlation formula. The results of this study found (1) peer social support was in the high category with an average score of 131.21 (72.9%) (2) the resilience of students who were victims of bullying was in the high category with an average score of 162.79 (72.35%) (3) there is a significant positive relationship between peer social support and the resilience of students who are victims of bullying with a correlation coefficient of 0.692 and a significance value of 0.000. So, these results indicate that the higher the peer social support, the higher the resilience, and vice versa.